Plant communities in a topographic catena of a dune area in the Conhelo department - La Pampa - Argentina (Semiárida, 2020)
This study pretends to distinguish the different communities that grow along a topographical profile, in a sandy area of the province of La Pampa. At the top of the hill there is a community codominated by Hyalis argentea and Elyonurus muticus (olivillal) In The upper slope it grows a dense and intermediate grassland dominated by Sorghstrum pellitum a very palatable warm grass (sorgastral). In the middle and low slope there are two different grass lands integrated by Bothriochloa springfieldii (pastizal) and Poa ligularis and Piptochaetium napostaense.